The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1159/000016344
|View full text |Cite
|
Sign up to set email alerts
|

Transcytosis and coenzymatic conversion of [<sup>57</sup>Co]cobalamin bound to either endogenous transcobalamin II or exogenous intrinsic factor in Caco-2 cells

Abstract: We have examined the intracellular route, coenzyme conversion and transcytosis rate of [57 Co]-labeled cobalamin (Cbl) in function of its presentation to the apical side of Caco-2 cells, either free or bound to intrinsic factor (IF). The free-presented Cbl was progressively bound to endogenous transcobalamin II (TCII) which may stem, in part, from a basolateral to apical passage. Its transcytosis was TCII-mediated as it was abolished when antibodies to TCII were added to the apical medium. The appar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 32 publications
(40 reference statements)
4
32
1
Order By: Relevance
“…Freund (INSERM U.381, Strasbourg, France). Cells were routinely grown as described previously [19]. DMEM medium containing 5 % FCS and no methionine (Met free medium) was supplemented with either 30 mg/l L-methionine (Met+), and/or 50 µM Homocystine (Hcy+), each of them with or without Cbl (Cbl+ or Cbl free) at the concentrations indicated in the text.…”
Section: Culture Conditionsmentioning
confidence: 99%
“…Freund (INSERM U.381, Strasbourg, France). Cells were routinely grown as described previously [19]. DMEM medium containing 5 % FCS and no methionine (Met free medium) was supplemented with either 30 mg/l L-methionine (Met+), and/or 50 µM Homocystine (Hcy+), each of them with or without Cbl (Cbl+ or Cbl free) at the concentrations indicated in the text.…”
Section: Culture Conditionsmentioning
confidence: 99%
“…Until now, the consequences of B12 deficiency in the brain have been difficult to evidence because of the experimental limitations of the classical cell models. Indeed, the minute amount of vitamin B12 needed by cells can be provided in vitro by B12 from the FCS, which can bind the ''autocrine'' B12 carrier protein, transcobalamin (TC) (3,4).…”
mentioning
confidence: 99%
“…The expression of oleosin in reticulum remains when oleosin is heterologously expressed in mammalian cells (6). TC is the protein that displays the highest affinity for B12; it is constitutively secreted into plasma to bind the circulating vitamin B12, internalized into cells via receptormediated endocytosis, and subsequently addressed in cytosol and mitochondria (3,4,7). We linked TC to the hydrophobic oleosin to sequester B12 in the cytosolic face of intracellular membranes.…”
mentioning
confidence: 99%
“…In the present study, Caco-2/HT29-MTX co-cultured cell model was used, which consists of both absorptive enterocyte-like Caco-2 cells and the mucus-producing goblet cell-like HT29-MTX cells. It is also confirmed that both of them have an IF-dependent fashion (32-35) and IF-independent fashion (29,(36)(37) for the transportation of VB12. Also, this cell model could be affected by some chemical reagent.…”
Section: Disscusionmentioning
confidence: 53%